The long road to effective court interpreting : international perspectives - Ozolins, Uldis (Language and Law / Linguagem e Direito, 2017)
While judicial systems and processes dier signicantly around the world, providing eective language services has faced very similar obstacles across dierent jurisdictions. Whether judicial authority is based on constitutional interpretation, or common law or codied systems, interpreting services in most jurisdictions are still poorly developed and coordinated. Provision of interpreting through such mechanisms as the Court Interpreters Act in the US are examined, as well as in common law systems without legislative basis, and the European attempt to standardise provision of legal interpreting in the EU member states. Improvements have been brought about by dierent actors – at times magistrates and judicial eorts, at times interpreter activism, at times more general political moves, or even the consequences of wider provision of language services not originating from the legal systems. It is important to foster alliances between interpreting interests and champions within the legal system to bring about meaningful change